In vitro biotransformation assays using fish liver cells: Comparing rainbow trout and carp hepatocytes - Bischof, Ina; Arnot, Jon A.; Jürling, Heinrich; Knipschild, Georg; Schlechtriem, Christian; Schauerte, Anna; Segner, Helmut (Frontiers in Toxicology, 2022)
Biotransformation assays using primary hepatocytes from rainbow trout, Oncorhynchus mykiss, were validated as a reliable in vitro tool to predict in vivo bioconcentration factors (BCF) of chemicals in fish. Given the pronounced interspecies differences of chemical biotransformation, the present study aimed to compare biotransformation rate values and BCF predictions obtained with hepatocytes from the cold-water species, rainbow trout, to data obtained with hepatocytes of the warm-water species, common carp (Cyprinus carpio). In a first step, we adapted the protocol for the trout hepatocyte assay, including the cryopreservation method, to carp hepatocytes. The successful adaptation serves as proof of principle that the in vitro hepatocyte biotransformation assays can be technically transferred across fish species. In a second step, we compared the in vitro intrinsic clearance rates (CLin vitro, int) of two model xenobiotics, benzo[a]pyrene (BaP) and methoxychlor (MXC), in trout and carp hepatocytes. The in vitro data were used to predict in vivo biotransformation rate constants (kB) and BCFs, which were then compared to measured in vivo kB and BCF values. The CLin vitro, int values of BaP and MXC did not differ significantly between trout and carp hepatocytes, but the predicted BCF values were significantly higher in trout than in carp. In contrast, the measured in vivo BCF values did not differ significantly between the two species. A possible explanation of this discrepancy is that the existing in vitro-in vivo prediction models are parameterized only for trout but not for carp. Therefore, future research needs to develop species-specific extrapolation models.